POTENSI PENGEMBANGAN KARBON BIRU DI PESISIR GUNUNG KIDUL: KAJIAN LITERATUR DAN OBSERVASI LAPANGAN - Mustofa, Ikrom; Islami, Nur Indah; Puspitasari, Rifcha Ayu Dian; Khaidar, Muhammad Al; Udzma, Naila Syafa'atul; Rizky, Rafli Eka (Universitas Pelita Bangsa, 2025)
Blue carbon refers to carbon stored in coastal and marine ecosystems such as mangroves, seagrass meadows, and salt marshes, which play an important role in climate change mitigation. This study aims to assess the potential for blue carbon development in the coastal area of Gunung Kidul Regency, which is dominated by karst landforms. The methods used include a review of literature related to blue carbon potential in Indonesia and field observations carried out at six coastal sites. The results show that the blue carbon potential in this area is limited due to physical characteristics such as steep karst cliffs and the absence of mangroves, salt marshes, and seagrass ecosystems caused by unsuitable coastal morphology. However, coastal vegetation such as Pandanus tectorius and Casuarina equisetifolia demonstrates relatively high carbon storage capacity and may serve as alternatives for local blue carbon strategies. These findings indicate that blue carbon development efforts in Gunung Kidul should focus on optimizing coastal vegetation adapted to the physical environment. In conclusion, although the limited presence of typical blue carbon ecosystems reduces the region’s storage capacity, opportunities still exist through enhancing the role of resilient coastal vegetation as part of ecosystem-based climate mitigation solutions.